Unexpected maspin immunoreactivity in Merkel cell carcinoma. Issue 1 (December 2015) - Turdean, Sabin; Gurzu, Simona; Jung, Ioan; Neagoe, Radu; Sala, Daniela
Abstract Merkel cell carcinoma (MCC) is a rare but aggressive cutaneous neuroendocrine tumor, which multifactorial etiopathogenesis seems to be related to ultraviolet radiation, Merkel cell polyomavirus (MCV), and immunosuppression. In this paper, we present three cases of diagnosed MCC in apparently healthy Caucasians, two of them located in a sun-exposed area. They represented 0.25 % of all cutaneous malignant tumors diagnosed in our department. In the first case, MCC was diagnosed in the frontal region of a 67-year-old male, the second case was located in the right thigh of a 55-year-old female, whereas the third case involved the upper trunk of a 62-year-old female. All of these cases were diagnosed in the pT1 stage, having a diameter smaller than 2 cm, but the invasion depth involved the hypodermis. Microscopically, they consisted of small cells with round-oval nuclei having finely dispersed chromatin and well-defined nucleoli. Immunohistochemically, the tumor cells displayed positivity for keratin 20 and neuroendocrine markers, being negative for keratin 7 and S100 protein. Maspin immunoreactivity was seen in cases 1 and 3. Not one of the cases expressed DOG-1 or even TTF-1. Furthermore, this is the first report in literature about maspin positivity in MCC that might be related to sun exposure.